Impact of vitamin D on physical efficiency and exercise performance - A review - Wicinski, M.; Adamkiewicz, D.; Adamkiewicz, M.; Sniegocki, M.; Podhorecka, M.; Szychta, P.; Malinowski, B. (Nutrients, 2019)
Vitamin D deficiency amongst athletes and the general population seems to be a prominent problem. The most recognized role of vitamin D is its regulation of calcium homeostasis; there is a strong relationship between vitamin D and bone health. Moreover, its concentrations are associated with muscle function and immune response in both the general and athletic populations. Vitamin D level is strongly connected with the presence of VDRs (vitamin D receptors) in most human extraskeletal cells. Expression of multiple myogenic transcription factors enhancing muscle cell proliferation and differentiation is caused by an exposure of skeletal muscles to vitamin D. The aim of this review is to summarize current understanding of the significance of vitamin D on exercise performance and physical efficiency, as well to analyze the impact of vitamin D on multiple potential mechanisms. More high-quality research studies, considering free 25(OH)D as a better marker of vitamin D status, the baseline level of 25(OH)D and multiple pathways of vitamin D acting and usage in athletes are required.